PEMBUATAN APLIKASI E-COMMERCE PRODUK PERTANIAN BERBASIS CONTENT MANAGEMENT SYSTEM (CMS) - Lexi M. Pendong; Robert Molenaar; Hildy Wullur; Herry F. Pinatik (Universitas Sam Ratulangi, 2015)
ABSTRACT With the current technology developments have made changes in all areas, including trade. Various activities can be done easily and quickly, including buying and selling activities. E- commerce is one of the technology in helping the buying and selling activities. Wide range of products are being sold using e-commerce such as clothes, shoes, bags, food up to ticket. The development of e-commerce is also changing so rapidly, the current CMS (Content Management System) began to be considered to be used to build e-commerce because it is easier and faster in providing information.Â North Sulawesi is one area that is famous for its agricultural products such as coconut, cloves and processed products such as palm sugar, coconut oil, and others. Making the application of e-commerce is expected to help provide information related to agricultural products as well as simpifiying the buying and selling activities.Â This study aims to create a CMS-based web applications and financial transactions (e-commerce). This research is expected to help the community and students in accessing and providing information related to agricultural products rapidly and extensively, as well as simplifying the buying and selling process via the Internet.